Investigating the students’ behavior towards the temptation to do academic misconduct in higher education: The moderation of religiosity - Rizki Hamdani; Dede Iskandar Siregar; Arif Pratama Marpaung; Raniyah Aulihati Gonggo; Umi Sulistiyanti (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2022)
The purpose of this study was to investigate the factors that influence cheating intention (CI) and cheating behavior (CB) on accounting students with Islamic religiosity (IR) as a moderating factor. This study used the theory of planned behavior (TPB) concept in predicting academic cheating. The sample of this study used a cluster sampling approach. The data collecting technique used a survey method with a questionnaire. The population of this study was accounting students at an Islamic university in Yogyakarta, Indonesia with a total of 146 respondents. Regression analysis was employed to test this hypothesis by using a structural equation modeling (SEM) approach using smart-PLS. The results of this study indicated that attitude toward cheating (ATC) and IR had a negative effect on CI, and perceived behavioral control (PBC) had a positive effect on CI and CB. However, it has no effect when moderated by religiosity. This finding also implied that religiosity was unable to moderate TPB to reduce students’ desire to commit academic misconduct. This paper contributes to the literature by providing empirical evidence of the moderating effect of religiosity on academic misconduct of students in higher education.